1994
DOI: 10.1016/0885-3924(94)90189-9
|View full text |Cite
|
Sign up to set email alerts
|

The stability of mixtures of morphine hydrochloride, bupivacaine hydrochloride, and clonidine hydrochloride in portable pump reservoirs for the management of chronic pain syndromes

Abstract: The physical and chemical stability of a combination of drugs commonly administered into the epidural or intrathecal space for the treatment of chronic pain was investigated. The concentrations of bupivacaine hydrochloride, morphine hydrochloride, and clonidine hydrochloride were measured using high performance liquid chromatography. The solutions were stored in reservoir bags for up to 90 days. No macroscopic or microbiological signs of precipitation, change in color, or contamination were observed, and pH re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…There are some indications that patients can obtain more effective pain control from intrathecal treatment, as morphine is supplied directly at the level of the spinal cord (6). Other medications, such as clonidine, nonsteroidal antiinflammatory drugs, neostigmine, ketamine, octreotide, and aspirin, can be added intrathecally to enhance the analgesic effects of morphine (7). By contrast, the hope that the intrathecal administration of opioids would substantially reduce the number of side-effects associated with oral morphine has not been fulfilled (8).…”
mentioning
confidence: 99%
“…There are some indications that patients can obtain more effective pain control from intrathecal treatment, as morphine is supplied directly at the level of the spinal cord (6). Other medications, such as clonidine, nonsteroidal antiinflammatory drugs, neostigmine, ketamine, octreotide, and aspirin, can be added intrathecally to enhance the analgesic effects of morphine (7). By contrast, the hope that the intrathecal administration of opioids would substantially reduce the number of side-effects associated with oral morphine has not been fulfilled (8).…”
mentioning
confidence: 99%
“…Morphine does not alter the pH or solubility of LA mixtures [5,16]. The stability and compatibility of such LA mixtures are proven to be safe in infusion systems [5,9,14,16,30] and safe when used clinically [14]. On the contrary this case and anoth- er case report [1] discovered bupivacaine deposits with unreactive necrosis in different human tissues (e.g.…”
Section: Introductionmentioning
confidence: 88%
“…Wulf et al 43 examined mixtures of bupivacaine 0.3%, morphine 6.7 mg/mL, and clonidine 0.03 mg/mL from portable pump reservoirs intended for intrathecal infusion. They found that at room temperature, these mixtures were microbiologically stable over a period of 90 days.…”
Section: The Hang-time Of Regional Anesthetic Compoundsmentioning
confidence: 99%
“…Much attention has been given to the assessment of chemical stability of local anesthetics alone or in combination with epinephrine or opioids. [38][39][40][41][42][43] These admixtures have been studied in both polyvinylchloride bags and in portable infusion pumps. In general, compounds commonly used in regional anesthetic practice, including lidocaine, bupivacaine, ropivacaine, morphine, fentanyl, and hydromorphone, are chemically stable for periods of weeks to months and are not the limiting factor in determining hang-time.…”
Section: The Hang-time Of Regional Anesthetic Compoundsmentioning
confidence: 99%